“CURITIBA POUCO SABE DO PARANÁ”: A AVENTURA DA REPORTAGEM LITERÁRIA EM NICOLAU (1987-1996) - HORST, SCHEYLA JOANNE (2017)
In this dissertation, we work with articles inserted in selected editions of the Nicolau newspaper (1987-1996), in order to verify the marked characteristics of the texts and to analyze the approximations between the Journalism and the Literature in this production. The Nicolau was a publication made possible by the Secretariat of Culture of Paraná State, in Brazil, and brought together writers, journalists, illustrators, photographers, poets, translators and researchers in a moment of political opening in Brazil, consolidating itself as an editorial product differentiated in the market at the time, including a very remarkable peculiarity there – having been elaborated by the Govern but with an unusual editorial freedom. The main objective of this work is to present how the New Journalism has inserted there promotes nonfiction reports that make interesting use of Memory and provide a more qualified cultural Reading of the Paraná, with attention to other places far from the Capital, Curitiba. To follow the path o our research, we use the method called Analysis of Content, within a qualitative perspective, finding in the Cultural Studies a theoretical support for the reflections. In the course, we did a thematization on the relationship between Journalism and Literature, recovering important occurrences in this relation, presenting the New Journalism as a striking movement and explaining our point of view characterizing as a work of Literary Journalism (a Brazilian concept and a variant of the concept by New Journalism) and dialoguing with many authors, as Edvaldo Pereira Lima, Felipe Pena, Norman Sims and Monica Martinez among them. In the next level, we analyzed 12 reports from several journalists selected in the Nicolau pages, based on categories established by us and, then, we revealed the incidence of the elements of the New Journalism. After indicating the cultural diversity highlighted in the texts, we made reflections about the use of the Memory through medium of communication, which provides reports that have repercussions until the present day, even two decades after the circulation of the newspapers ends. As a Place of Memory (in the vision of Pierre Nora), the newspaper brings to the surface a forgotten Paraná. Finally, we conclude the dissertation by recapturing the findings of this research in a critical and purposeful way, no just looking the past but we also try to draw lessons for the future of the Journalism.